Evaluation of ESP Pump Size-up on Marley Field Production - Tanpasya, Alexander; Arizona, Rafil; Elfiano, Eddy; Anggara, Fajar (UIR PRESS, 2022)
Field or Field Marley is one of the fields in the work area of ​​PT. Pertamina Hulu Rokan, which is located in Riau Province, has entered the brownfield phase and has a high water cut rate. This condition made the company start a new step by making a size-up on the pump in the Marley well. However, after the Size-Up program was carried out there were several wells that failed, therefore in this study, the researcher will do a re-calculation to find out how far the success of the Size-Up program has been. After the Size-Up program was carried out at the Asmud well in the Marley field, the results obtained as much as 68% success, which is below the minimum target which should be above 100%. It is known that the pump installed in the Asmud well is a Centrilift 400P10 pump with a pump range of 650-1400 bfpd specifications, motor power 42 HP, electric current 53 A, voltage 475 V, and efficiency of 88.4%. Well data can be in the form of a 93% water cut, with an sfl value of 184 ft and a wfl of 307 ft, a pwf of 383.33 psi, and an API value of 34. Based on these parameters, the Inflow Performance Relationship (IPR) curve can be analyzed. it is analyzed that the Asmud well is in a down thrust condition where the pump is in the minimum range. Therefore, the researcher suggests that a Size-Down pump be carried out using a Centrilift 400P8 60 Hz pump with a specification range of 550-1200 bfpd which is in accordance with the production capacity of the Asmud well.